2003
DOI: 10.1046/j.1365-3156.2003.01053.x
|View full text |Cite
|
Sign up to set email alerts
|

Inland valley rice production systems and malaria infection and disease in the savannah of Côte d'Ivoire

Abstract: SummaryIn sub-Saharan Africa, lowlands developed for rice cultivation favour the development of Anopheles gambiae s. l. populations. However, the epidemiological impact is not clearly determined. The importance of malaria was compared in terms of prevalence and parasite density of infections as well as in terms of disease incidence between three agroecosystems: (i) uncultivated lowlands, ÔR0Õ, (ii) lowlands with one annual rice cultivation in the rainy season, ÔR1Õ and (iii) developed lowlands with two annual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 13 publications
2
40
0
Order By: Relevance
“…27 Associations between agricultural activities such as land clearing and production of crops such as cotton and sugar cane and having malaria have been reported. [11][12][13][14][15] Sugar cane and cotton cultivation have been associated with having malaria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Associations between agricultural activities such as land clearing and production of crops such as cotton and sugar cane and having malaria have been reported. [11][12][13][14][15] Sugar cane and cotton cultivation have been associated with having malaria.…”
Section: Discussionmentioning
confidence: 99%
“…11 Cultivation of crops that require considerable irrigation, such as rice, cotton, maize, and sugar cane, have been associated with an increased risk for developing malaria. [12][13][14][15] Studies in central Côte d'Ivoire reported an association between an interruption in irrigated-rice cultivation and changes in malaria transmission, decreases in Plasmodium prevalence, and the number of malaria cases. 16,17 With the goal of increasing agricultural production in several developing countries, arid land has been reclaimed and artificial irrigation schemes have been created.…”
mentioning
confidence: 99%
“…This phenomenon can be explained due to the better economic and social conditions of the communities living near the irrigation schemes, where more reliable health structures, better housing conditions and more resources to be spent in vector control and efficient treatments and preventive measures exist. This was verified in stable transmission areas of paddy fields in the Ivory Coast 40 , Cameroon 4 , and in northern Tanzania 45 . In the last example, although An.…”
Section: Africamentioning
confidence: 59%
“…Brazil, China, Colombia, India, Peru and Congo are the countries with the greatest hydroelectric potential unexploited, with the Amazon, Congo and Mekong basins being the ones that can be exploited best for this purpose 42 . 40,000 large dams and other 800,000 man-made lakes of smaller size were estimated to have been built by 2001 49 .…”
Section: Damsmentioning
confidence: 99%
“…In most settings of endemic infection, adults have developed a functional immune response to infection, and the incidence of measured elevated body temperatures associated with significant increases in parasite density is low compared to that in pediatric populations (57,93,113,121). Nevertheless, the term "fever" is often used by adults to describe clinical conditions subsequently managed as malaria.…”
Section: Community Definitions Of Malaria and Fevermentioning
confidence: 99%